Physicochemical, Structural, Thermal, and Rheological Properties of Mango Seed Starch from Five Cultivars - Ndahita De Dios-Avila; Mario Alberto Morales-Ovando; Paul Baruk Zamudio-Flores; Juan Carlos Bustillos-Rodríguez; Magali Ordóñez-García; Kati Beatriz Medina-Dzul; Teresa Romero-Cortes; Jaime Alioscha Cuervo-Parra; Juan Manuel Tirado-Gallegos (Polysaccharides)
Large quantities of seeds are generated and discarded during agro-industrial mango processing. However, mango seeds still contain valuable components such as starch, which has applications in various industries. This study aimed to obtain and characterize starches from the seeds of five mango cultivars (Ataulfo, Manililla, Piña, Tapana, and Tommy Atkins). The isolated starches were evaluated for their physicochemical, morphological, structural, thermal, and rheological characteristics. The starches showed creamy white colorations, and their granules had spherical and oval shapes. This starch source contains a high percentage of apparent amylose, greatly influencing its thermal, rheological, and functional properties. Structural and molecular studies showed that all starches presented an A-type X-ray diffraction pattern, impacting their water absorption and viscosity. The transition temperatures were relatively high, which could be influenced by the length of the amylopectin chains and their intermediate components, the apparent amylose content, and other components such as lipids and anomalous amylopectin. The starches evaluated behaved as pseudoplastic materials, while oscillatory tests revealed that the pastes formed with mango starches are more elastic than viscous. In conclusion, research on the seed starch properties of different mango cultivars provides interesting results for their potential application in foods. It could contribute to the value-added processing of mango seeds as a potential starch source.